Pemanfaatan Trichoderma sp. sebagai Agens Hayati untuk Pengendalian Penyakit Layu Fusarium dan Pembuatan Trichokompos di Desa Cenrana Baru - Widiati, Bibiana Rini; Herwati, Andi; Sadat, Moh. Anwar; Awaluddin, Awaluddin; Abdillah, Abi Akbar (Abdimas Universal, 2026)
Red chili peppers hold substantial economic potential but face various challenges that affect production outcomes. One of the main issues encountered by the Sejati farmer group in Cenrana Baru Village is Fusarium wilt disease, which poses a serious threat to chili cultivation and can significantly reduce yields if left unmanaged. Trichoderma sp. is known to be effective in suppressing soil-borne pathogens while also enhancing plant growth through antagonistic mechanisms and improvement of soil fertility. This community service program aims to enhance the farmers’ knowledge and skills regarding the benefits and techniques of propagating Trichoderma sp. as a biological control agent and to facilitate the production of trichocompost. The implementation stages include preparation, socialization, training, and mentoring in the propagation of Trichoderma sp. and the production of trichocompost. The training activities were carried out directly with the Sejati farmer group and the community of Cenrana Baru Village. Improvements in farmers’ knowledge and skills were analyzed both qualitatively and quantitatively. The qualitative analysis involved observing changes in participants’ behavior and understanding, while the quantitative analysis was obtained from pretest and posttest questionnaires, which were converted into percentage values and subsequently described. The results indicate strong enthusiasm from the Sejati farmer group, who actively practiced Trichoderma sp. propagation and trichocompost production. There was a noticeable increase in knowledge and skills based on the comparison of pretest and posttest scores. This PKM activity is expected to strengthen the independence of the Sejati farmer group in controlling Fusarium disease and implementing sustainable chili cultivation practices.